Incidence of mortality and its predictors among septic shock patients admitted to the intensive care unit of comprehensive specialized hospitals in the northwest of Amhara, Ethiopia - Ayenew Mekuria, Tesfaye; Liyew Wudu, Bikis; Zegeye, Alebachew Ferede; Eshete Tadesse, Eyob; Demis Nimani, Teshome (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction Septic shock is a global health issue causing high mortality rates in intensive care units, with limited evidence in Africa, including Ethiopia, regarding its incidence and predictors. The aim of this study was assess the incidence and predictors of mortality among patients with septic shock admitted to the ICU of Comprehensive Specialized Hospitals of the Northwest Amhara region. Methods A study involving 386 ICU patients with septic shock from 2019 to 2023 was conducted using a random sampling method and structured data extraction tool. Data was analyzed using EpiData and STATA, with variables selected for multivariate analysis. Result The overall incidence rate of septic shock was 10.4 per 100-person day of observation with a median survival time of 7, days and the proportion of deaths during the study period was 58.29%. In multivariate Cox proportional regression analysis, age 40–59 years (HR: 1.77, p = 0.005), age > 60 years (HR: 3.52, p < 0.001), delay ICU admission (HR: 1.93, p = 0.001), low MAP (HR: 2.56, p < 0.001), comorbidity (HR: 2.74, p < 0.001), complication (HR: 1.87, p = 0.012), ALF (HR: 1.84, p = 0.037), no pathogen identification (HR: 1.69, p = 0.035) were found significant predictors of mortality for patients with septic shock in the ICU. Conclusion The incidence of mortality in patients with septic shock admitted to the ICU was high and the main predictors were age> 60 years, low MAP, comorbidity, and delay ICU admission >6 h, Hence, Early recognition and appropriate treatment recommended by the International Sepsis Survival Campaign guideline should be implemented.